2021
DOI: 10.3389/fpls.2021.628969
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolomic and Transcriptomic Studies Reveal Key Metabolism Pathways Contributing to Freezing Tolerance Under Cold Stress in Kiwifruit

Abstract: Cold stress poses a serious treat to cultivated kiwifruit since this plant generally has a weak ability to tolerate freezing tolerance temperatures. Surprisingly, however, the underlying mechanism of kiwifruit’s freezing tolerance remains largely unexplored and unknown, especially regarding the key pathways involved in conferring this key tolerance trait. Here, we studied the metabolome and transcriptome profiles of the freezing-tolerant genotype KL (Actinidia arguta) and freezing-sensitive genotype RB (A. arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 49 publications
3
18
0
Order By: Relevance
“…With the frequent occurrence of extreme weather, climate has become a major factor affecting the high yield of crops. Multiple responses to cold stress in plants have been shown to reflect changes in transcription and metabolism ( Zhao D. Q. et al, 2019 ; Raza et al, 2021 ; Sun et al, 2021 ). In this study, we identified 10,931 DEGs and 657 DEMs in positive ion mode and 390 DEMs in negative ion mode by multi-omics analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the frequent occurrence of extreme weather, climate has become a major factor affecting the high yield of crops. Multiple responses to cold stress in plants have been shown to reflect changes in transcription and metabolism ( Zhao D. Q. et al, 2019 ; Raza et al, 2021 ; Sun et al, 2021 ). In this study, we identified 10,931 DEGs and 657 DEMs in positive ion mode and 390 DEMs in negative ion mode by multi-omics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In Nicotiana tabacum , differences exist in energy metabolism and hormone metabolism between cold-resistant and cold-sensitive cultivars ( Jin et al, 2017 ). A study on kiwifruit showed that the codeinone reductase and chalcone isomerase genes, nucleotide metabolism, and phenolic acid metabolism pathways participate in the regulation of freezing tolerance ( Sun et al, 2021 ). Furthermore, Zhao Y. et al (2019) demonstrated that differentially expressed genes (DEGs) and differentially expressed metabolites (DEMs) in wheat were significantly enriched in abscisic acid/jasmonate (ABA/JA) signaling and proline biosynthesis under cold stress.…”
Section: Introductionmentioning
confidence: 99%
“…When plants are subjected to freezing stress, photosynthesis will be inhibited and cell structure destroyed, resulting in oxidative damage, metabolic disorder, cell damage, and other phenomena [9][10][11]. Simultaneously, plants will express a large number of resistance genes and metabolites when subjected to freezing stress [12].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics is currently being utilized to qualitatively and quantitatively evaluate all metabolites to offer an advanced assessment technique of the cellular state. The HPLC-MS/MS-based metabolomics are widely used to profile metabolites involved in the physiological responses to environmental challenges in plants ( Liu et al, 2021 ; Sun et al, 2021 ; Xiong et al, 2022 ). In the present study, we utilized a widely targeted metabolomics approach using the UPLC-MS/MS analytical platform to analyze the metabolite changes of P. nutans under cold stress ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%